Selected proceedings of the 9th world congress on transport research (Elsevier, 2003)
CD-ROM. No other transportation conference has the scope and authority of the triennial World Conference on Transport Research. These proceedings present 143 papers from the 9th conference (Seoul), representing the latest in transportation research from around the world, and covering a broad range of topics of current importance within transportation. The papers offered here were selected from some 800 presented at the conference, and have been fully peer reviewed and revised in accordance with the high standards set by previous WCTR proceedings.